Increasing returns to education and the skills under-investment trap - Alison L. Booth; Melvyn G. Coles (Institute for the Study of Labor (IZA), 2005)
We model educational investment and labor supply in a competitive economy with home and market production. Heterogeneous workers are assumed to have different productivities both at home and in the workplace. We investigate the degree to which there is under-investment in human capital, and examine the deadweight losses that accrue via distortionary taxes. We show that there are increasing returns to education at the participation margin, and that deadweight losses are most severe for workers located here. Although the social planner's optimum implies the worker should choose a high level of education and participate in the market sector, instead the worker chooses not to invest in human capital and either non-participation or partial participation in market-sector work. A severe deadweight loss is generated by this substitution effect. Those individuals most likely to be in this trap are those types with large enough home productivity, who are likely either to be involved in home production or to be characterized by a strong preference for other non-market sector activities. home production ; labor supply ; returns to education ; income tax
Keywords: H24; J13; J24; J31; J42; 330